Nitrocellulose and Nanomaterials: Graphene-based High Performance Propellants - Callaghan, Ciaran (Cranfield University, 2017)
Poster presented at the 2017 Defence and Security Doctoral Symposium.The superior strength, mechanical, thermal and electrical properties of graphene has attracted significant attention from the Defence community, including the Ministry of Defence and the European Defence Agency. This PhD programme seeks to investigate the fundamental chemical interactions of graphene with nitrate esters in order to identify its suitability for future application in energetic materials. It is envisaged that this will be conducted by applying various spectroscopic (IR, RAMAN, NMR), thermal (DSC, TGA) and mechanical (DMA) techniques. Achieving such an understanding of this chemistry will not only fill gaps in the knowledge pertaining to currently used ballistic modifiers, but also provide exploitable data for future rocket and gunnery weapons developments.
Keywords: 'Nitrocellulose'; 'Nanomaterial'; 'Propellant'; 'DSDS17 poster'; 'DSDS17'; 'Defence Studies'; 'Nanomaterials'